Biodegradable, eco-friendly, and hydrophobic drinking straws based on delignified phosphorylated bamboo-gelatin composites - Rai R.; Ranjan R.; Kant C.; Dhar P. (My University, 2025)
Single-use plastic straws have become one of the major global challenges due to its abundant consumption, non-degradability, and accumulation as a waste causing detrimental effects on humans, aquatic life, and the ecosystem. Recently, plastic straws have been replaced with paper straws, however, it has multiple shortcomings, such as poor water stability, wet strength, utilize non-degradable adhesives or coatings, and are of single-use only. Therefore, finding new alternative straws which are sustainable, biodegradable, mechanically robust, and water-stable is the need of the hour. The current work reports the fabrication of gelatin-infiltrated and crosslinked, mechanically robust, biodegradable, and hydrostable straws prepared using delignified phosphorylated bamboo (DPB). The presence of both charge-based electrostatic interactions (positively charged gelatin and negatively charged phosphate in DPB) and hydrogen bonding were responsible for uniform distribution of cross-linked gelatin in porous bamboo, which was optimized by varying pH and gelatin concentration. The drinking straws infiltrated with 7.5% gelatin at pH 4, shows high mechanical strength of 138 MPa, Young's modulus of 1.38 GPa, hydrophobic surface wettability with a contact angle of 103.3°, and water stability upto ∼ 24 h. The bamboo-gelatin straws also show improved biodegradability (degradation up to 98% in 36 days), with a reduction in global warming potential by 54% and 17.6% less damage to ecosystems during end-of-life, compared to plastic straws. The migration values of straws were within the standard limits when in contact with various types of simulants such as acidic, alkaline, alcoholic, carbonated, and fatty foods tested in temperature range of 0–95 °C, making it suitable for both hot and cold beverages. In the present work, bamboo-gelatin straws derived from abundantly available biomass have the required properties to become a sustainable alternative to single-use plastic or paper straws, a step towards reducing global plastic waste and our dependency on petroleum-based products. © 2023 Elsevier B.V.